«Russians outside of Russia: Social and Economic Thoughts» series (continuation). Maslov S. S. Collective Farms (Kolkhozes) in Russia - Александр Александрович Куракин (Journal of Economic Sociology, 2010)
This review of Alexander Kurakin’s from the series “Russians outside of Russia: Social and Economic Thoughts” is about a founder of Peasant Party S. Maslov’s book written at the time of collectivization (1937). Maslov argued that collectivization was a new and unique phenomenon entailed by the Socialist system. What is speciﬁ c about it? Why did Russia face the overall collectivization? What beneﬁ ts did kolkhozes bring to the authorities and peasants? The presented review provides us with answers for these and some other important questions. The Maslov’s book is based on rich empirical evidences including eyewitnesses’ narratives, the Soviet mass media, Communist party leaders’ speeches, etc.